DETERMINANTS OF INCOME FOR FASHION MSMEs IN DENPASAR CITY, BALI PROVINCE - Akhmad Sohibul Wafa; I Nyoman Wahyu Widiana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
In the structure of Indonesia’s economy, Micro, Small, and Medium Enterprises (MSMEs) constitute the majority of business entities and make a significant contribution to the gross domestic product. This study aims to examine the effect of business capital, labor, e-commerce utilization, business duration, and working hours on the income of fashion MSMEs in Denpasar City, Bali Province, both simultaneously and partially. This research employs a quantitative approach using both primary and secondary data sources. Primary data were collected through questionnaires distributed to 99 MSME owners, selected using purposive sampling. The data collection instrument was a questionnaire, and the data analysis method applied was multiple linear regression. The findings indicate that, simultaneously, business capital, labor, e-commerce utilization, business duration, and working hours have a significant effect on the income of fashion MSMEs in Denpasar City. Partially, business capital, labor, e-commerce utilization, and business duration have a positive and significant effect on income. However, working hours show a negative and significant effect on income, suggesting that an increase in working hours without corresponding efficiency or productivity may adversely impact business performance. The study provides policy insights for optimizing capital use, enhancing labor productivity, promoting digital adoption, and managing working hours effectively to boost MSME income in the fashion secto.